The development and properties of biodegradable and sustainable polymers. - Salit, Mohd Sapuan; Japar, Sahari (2012)
This paper focusses on the review of development and properties of biodegradable and sustainable polymers which become an attracting area in materials science research. The basic properties and recent development in sustainable polymers such as poly lactide (PLA), thermoplastic starch (TPS), cellulose and polyhydroxyalkanoates (PHAs) were reviewed in this paper. This paper also provides a general overview of some important topics in biopolymers such as chemical, processing, mechanical and physical properties.